(untitled) (Journal of Pathology of Nepal, 2024)
Background: Hypersegmented neutrophils are one of the earliest indicators of megaloblastic anemia rather than raised MCV. Hypersegmented neutrophils are also seen as a part of myeloproliferative and myelodysplastic syndromes. Uremia, hyperthermia, and many drugs are also known to produce neutrophilic hypersegmentation. Congenital condition which is autosomal dominant in inheritance is known to cause hereditary hypersegmentation. We aimed to evaluate causes of hypersegmentation in peripheral smear apart from already known causes. Materials and methods: The study was conducted for three years. EDTA samples collected in the hematology lab were evaluated for hypersegmentation and other associated findings by examining the giemsa-stained peripheral smears. The study population was classified according to the size of red blood cells i.e. normocytic, microcytic, and macrocytic population. Other associated factors like chronic infections, drug history, and other significant history were also recorded on a predesigned proforma. Results: After obtaining written, understandable, informed consent for this pilot project, 410 volunteers were enrolled. Macrocytic red blood cells were seen in more than 50% of cases. Cases with normal peripheral smears were evaluated for hidden Vitamin B12 deficiency and other associated factors. Approximately 90% of these had low Vit B12 levels so neutrophilic hypersegmentation was the first evident sign of megaloblastic anemia. Vit B12 levels less than 200 pg/ml had a significant correlation with neutrophilic hypersegmentation (p-value <0.05). Conclusions: The study was planned to evaluate causes of Neutrophilic hypersegmentation other than existing causes however the results were inconclusive.